2009
DOI: 10.4103/0377-4929.54987
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow biopsy in non-Hodgkin lymphoma: A morphological study

Abstract: Critical examination of BM biopsies can increase the diagnostic accuracy, thereby contributing to the prognosis and appropriate treatment modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 0 publications
5
20
1
Order By: Relevance
“…Kumar A showed involvement by lymphoma on biopsy in 27 cases (55.10%). 13 Unilateral positivity was found in four cases (14.81% cases). The overall incidence of marrow involvement by NHL was 55.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Kumar A showed involvement by lymphoma on biopsy in 27 cases (55.10%). 13 Unilateral positivity was found in four cases (14.81% cases). The overall incidence of marrow involvement by NHL was 55.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Increased mixed pattern of (nodular and interstitial) in Kumar et al, study can be also attributed to the inclusion of high number of CLL patients. [10,13] In the current study 15 [9] In the current study, patients with positive Bsymptoms showed bone marrow infiltration were (55%) and patients with negative Bsymptoms were (45%). Difference between patients with or without B-symptoms was statistically non-significant as regards bone marrow infiltration (p: 0.387).…”
Section: -138-mentioning
confidence: 74%
“…[8] Also in a study by Kumar et al, who report that the incidence of DLBCL in his work was 9/19 (47.37%) that invade the bone marrow. [10] In other work by Elrefaey et al, DLBCL cases that showed infiltration of bone marrow were 8/59 (13.5%). [9] Also study by Campbell et al, who reported that (11%) of DLBCL involved the marrow.…”
Section: -138-mentioning
confidence: 89%
“…Though it can also occur in children and young people in rare cases. DLBCL is an aggressive tumor which can arise in any part of the body (6), and the first sign of this illness is typically the observation of a rapidly growing mass, sometimes the swelling is associated with fever, weight loss, and night sweats. The most typical symptom at the time of diagnosis is a mass that is rapidly developing which is located in a part of the body that includes multiple lymph nodes (7).…”
Section: Introductionmentioning
confidence: 99%
“…Bilateral iliac crest BM biopsies and step sections for morphological view are advocated for optimal specimen and detection of small focal lesions accompanied by fibrosis that may not be readily detected in aspirate smear preparations, thereby increasing the yield of possible diagnosis and becoming superior to aspiration study (6). …”
Section: Introductionmentioning
confidence: 99%